Síndrome de Papillón-Lefévre. Hiperqueratosis palmo-plantar y enfermedad periodontal agresiva. Caso clínico - Morales-Vargas, Milton (Odovtos - International Journal of Dental Sciences, 2012)
The Papillon-Lefévre Syndrome is a rare syndrome that appears in 1 to 4 live births per millon. It is characterized by erythematous palmoplantar hyperkeratosis and agresive periodontal disease that affect both dentition and lead to the total loss of teeth at an in early age. The present article refers to the diagnosis of the syndrome in four sisters residents of Llano Grande de Cartago, the initial treatment took place at the Center of Specialities of Dentistry and Dermatology in the Calderon Guardia Hospital. The early identification of the syndrome plays an important role in prolonging the permanency of the teeth for a longer period in the oral cavity.